Pronunciation Errors Made by Javanese EFL Learners in Pronouncing English Vowels and Consonants - Dilla Maryam; Titi Rokhayati; Edi Sunjayanto Masykuri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Accurate pronunciation is essential for effective spoken communication in English; however, many EFL learners continue to experience pronunciation difficulties. Despite previous studies on pronunciation problems, limited research has comprehensively examined the relationship between contributing factors, recurring patterns, and error types among Javanese EFL learners, whose first language presents distinctive phonological differences from English. This qualitative case study investigates pronunciation errors among Javanese EFL learners by examining contributing factors, recurring patterns, and error types. Seven Javanese-speaking EFL learners at Universitas Muhammadiyah Purworejo were selected through purposive sampling. Data were collected through pronunciation tasks and semi-structured interviews and analyzed using thematic analysis with data triangulation. The findings reveal that pronunciation errors are influenced by linguistic factors, including first language interference and phonological differences, as well as non-linguistic factors such as limited exposure, lack of practice, low confidence, anxiety, and low motivation. These factors contribute to recurring patterns of substitution, simplification, and avoidance, which are reflected in vowel substitution, diphthong simplification, vowel length confusion, consonant substitution, and voicing errors. The findings contribute to pronunciation teaching by emphasizing explicit instruction, increased exposure, regular practice, and supportive learning environments to improve pronunciation accuracy among Indonesian EFL learners.